1654. Chickenpox Outbreak in a Tribal District Rayagada, Odisha, India: Warrants Need for Vaccination - Salomi. Kerketta, Anna (Open Forum Infect Dis, 2019)
BACKGROUND: Chickenpox or varicella is caused by Varicella zoster virus. In India chickenpox outbreak is not uncommon as the vaccination against varicella is not included in the program. We report, chickenpox outbreak in a tribal district Rayagada, Odisha state of India a South Asian country. The outbreak investigation was undertaken to assess the characteristics and determinants of the outbreak and make appropriate recommendations for control and prevention of further transmission. METHODS: A door to door survey was made for case finding and line listing with detailed travel, exposure and vaccination history. Qualitative research tools including key informant’s interview and focus group discussion were undertaken to understand community behavior and practice. Intravenous blood samples were collected for serological test to detect antibody to varicella-zoster virus. RESULTS: A total of 59 individuals out of 767 residents were affected with chickenpox in this outbreak with an attack rate of 8.73 per 100 populations. Age distribution indicated 69.5% belonged to the age group less than 14 years. No severe complication was reported. Blood sample of 33 case-patients was tested for Varicella zoster virus IgM antibodies and 24 (72.7%) found seropositive. The primary case was an 11-year-old girl who contracted infection in her residential school. None of the community members had received vaccination against chickenpox. Qualitative research indicated traditional beliefs and remedies prevailing in the communities that prevented case isolation and the modern treatment. CONCLUSION: The study highlights the need for regular training of peripheral health workers for an effective awareness campaign to change beliefs and traditional practice and vaccination against Varicella zoster virus for prevention of such outbreaks. DISCLOSURES: All authors: No reported disclosures.